MEDIA PEMBELAJARAN DIGITAL E-FLASHCARD DALAM PEMBELAJARAN MEMBACA PERMULAAN - Rizka Hidayatul Husna; Nur Azmi Alwi; Firman; Desyandri4 (EDU RESEARCH, 2024)
Early reading skills are a crucial foundation in elementary education, as they relate to the ability to comprehend written texts and information. This study aims to develop technology-based learning media in the form of E-Flashcards to enhance the early reading skills of first-grade elementary students. The research employs the Systematic Literature Review (SLR) method, involving a systematic analysis of articles from 2020–2024 relevant to the implementation of E-Flashcards in early reading instruction. The results indicate that E-Flashcards significantly improve students' early reading abilities. This media not only helps students recognize letters, words, and sentences but also increases their learning motivation through interactive and engaging features. Moreover, E-Flashcards have proven effective in various learning contexts, including remote learning. Students' responses to the use of this media are highly positive, as it supports enjoyable and easily understandable learning experiences. The study recommends further development of E-Flashcards for various subjects and grade levels, as well as enhanced teacher training to optimize the use of this media. The integration of E-Flashcards is expected to be an innovative solution in supporting technology-based learning in the digital era.